The solubility of oxygen in water and saline solutions - Bok, F.; Moog, H. C.; Brendler, V. (Frontiers in Nuclear Engineering, 2023)
Oxygen is one of the key reaction partners for many redox reactions also in the context of nuclear waste disposal. Its solubility influences radionuclides’ behavior, corrosion processes and even microbial activity. Therefore, a reliable calculation of the solubility of molecular oxygen in aqueous solutions is relevant for any safety assessment. Available geochemical speciation and reactive transport programs handle these data very differently. In some codes the hypothetical equilibrium between dissolved oxygen and water is used to balance redox reactions. Equilibrium constants are given in “temperature grids” for up to 573.15 K. In other cases, temperature functions for the solubility of gaseous oxygen in water are given, without any reference to a valid temperature range. These settings become even more complicated when used in the context of modeling equilibria in high-saline solutions applying the Pitzer formalism. This raised the question about the experimental foundation of equilibrium constants given in such data files and their validity for the solubility of molecular oxygen in saline solutions. For this article, a thorough literature review was conducted with respect to the solubility of molecular oxygen in pure water and saline solutions. From these primary experimental O2 solubility data a temperature-dependent Henry’s law function as well as temperature-dependent binary and ternary Pitzer ion-interaction coefficients were derived. An internally consistent set of thermodynamic data for dissolved oxygen is presented, along with statements about its validity in terms of temperature and, as far as Pitzer interaction coefficients are concerned, of solution composition. This self-consistent activity-fugacity model containing thermodynamic data, Henry's law temperature equation, and Pitzer interaction coefficients is capable of providing a more accurate description of redox transformations, allowing a reduction of conservatism in safety assessment calculations, not only in the context of a nuclear repository. The model reproduces well the reliable experimental data available, and is capable to predict the oxygen solubility in complex solution media. The temperature functions used to describe Henry's constant and the Pitzer interaction coefficients are consistent with the implementation in commonly used geochemical computational programs, allowing direct use without further modification.